Mandat przedstawicielski a tzw. klauzula czechosłowacka (rozważania na tle przepisów Konstytucji Ukrainy) - Eckhardt, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The Czechoslovak Clause is the institution of the parliamentary law used to deprive the deputy who has left the parliamentary group of his mandate. It can be used as an effective tool for preservation of party discipline, what is one of the main problems of the contemporary parliamentarism. The author of the paper analyses implementation of the Czechoslovak Clause in the constitution of Ukraine after the amendments of 2004. Effects of the Czechoslovak Clause on the representative mandate considered as an power of attorney for expressing the will of the nation in the parliament granted by voters for a certain period of time are investigated.
Keywords: parliamentary group; party discipline; representative mandate